Mapping Saturn's Nightside Plasma Sheet Using Cassini's Proximal Orbits. Issue 14 (20th July 2018) - Sergis, N.; Achilleos, N.; Guio, P.; Arridge, C. S.; Sorba, A. M.; Roussos, E.; Krimigis, S. M.; Paranicas, C.; Hamilton, D. C.; Krupp, N.; Mitchell, D. G.; Dougherty, M. K.; et al.
Abstract: Between April and the end of its mission on 15 September, Cassini executed a series of 22 very similar 6.5‐day‐period proximal orbits, covering the mid‐latitude region of the nightside magnetosphere. These passes provided us with the opportunity to examine the variability of the nightside plasma sheet within this time scale for the first time. We use Cassini particle and magnetic field data to quantify the magnetospheric dynamics along these orbits, as reflected in the variability of certain relevant plasma parameters, including the energetic ion pressure and partial (hot) plasma beta. We use the University College London/Achilleos‐Guio‐Arridge magnetodisk model to map these quantities to the conjugate magnetospheric equator, thus providing an equivalent equatorial radial profile for these parameters. By quantifying the variation in the plasma parameters, we further identify the different states of the nightside ring current (quiescent and disturbed) in order to confirm and add to the context previously established by analogous studies based on long‐term, near‐equatorial measurements. Plain Language Summary: Highly energized charge particles are trapped in the rapidly rotating magnetic cavity (the magnetosphere) of Saturn. Subject to the strong centrifugal potential, these particles, with energies in the order of few keV to few MeV, deform the dipole magnetic field of the planet and form an equatorial disk shaped structure, the magnetodisk. In this study we present how a theoretical magnetodisk model can be combined with Cassini particle data and accurately describe the field and plasma properties of the Saturnian magnetodisk. We further demonstrate how the previously observed variability of the electric current encircling the planet, the ring current, is also clearly identified in the measurements obtained during the 22 Cassini proximal orbits of nearly identical geometry. We find that this short‐time temporal variability is comparable to the documented local time asymmetry of the ring current. Key Points: The UCL/AGA (University College London/Achilleos‐Guio‐Arridge) magnetodisk model describes very well the additional magnetic field in the Saturnian magnetodisk and can project high‐latitude data to the equator The previously reported quiescent and disturbed states of the Saturnian ring current are also identified in the 6.5‐day period of the Cassini proximal orbits The temporal (6.5‐day) variability in the nightside magnetosphere of Saturn during Cassini's proximal orbits is comparable to the average local time asymmetry